FRI0024 Multiplatform metabolomic study of cd4+ cells after methotrexate and infliximab treatment: focus on safety and tolerability profiles. (23rd January 2014) - Chimenti, M. S.; Ranalli, M.; Saraceno, R.; Teoli, M.; Perricone, R.; Candi, E.; Melino, G.
Abstract : Background: Activated CD4+ cells comprise a large proportion of inflammatory cells involved in the development of rheumatoid arthritis (RA). Inflammatory cytokines, as tumor necrosis factor-a (TNFa), have also been implicated in the establishment and progression of joint destruction. Treatments for RA include synthetical and biological disease modifying anti-rheumatic drugs (DMARDs), as methotrexate (MTX) and TNFa-inhibitors, as infliximab. Cellular effects can be evaluated by metabolomics with measurement of ideally all endogenous metabolites. Objectives: Evaluation in CD4+ cells, from a multiplatform metabolomic study, of MTX and infliximab treatment in order to investigate the metabolomic features. Methods: Blood samples from 5 healthy controls were collected for metabolomic study. CD4+ cells were isolated by magnetic separation using CD4 MicroBeads from peripheral blood mononuclear cells, divided in 5 different groups and cultured for 24 hours: 1. CD4+ T cells as control, 2. CD4+ T cells treated with MTX at the dosage of 0.01 mM, 3. CD4+ T cells treated with MTX at the dosage of 0.1mM, 4. CD4+ T cells treated with infliximab at the dosage of 1 µg/ml, 5. CD4+ T cells treated with IgG1k at the dosage of 1µg/ml as control of Infliximab. A total of 25 cell samples were analysed using Metabolon's standard extraction method. Results: Ribulose was reduced with decrease in glycolysis and inhibition of phosphofructose kinase 1 (PFK1) by MTX (p<0.05). This reflects CD4+ cells effort to increase the production of cellular reducing power (NADPH) to offset stress exerted by MTX. Isovalerylcarnitine, linked to proteolytic enzymes and calpain system, was increased by MTX (p<0.05). Both calpain and caspase systems lead to cytochrome activation and promote early apoptosis. Hypotaurine, an antioxidants in vivo, was increased by both MTX and Infliximab (p<0.05). Glutarate (pentanedioate) was reduced by infliximab(p<0.05). This agent is linked to oxidized phospholipids and proteins; measurement of protein-bound phosphate and long-chain fatty acids may be useful for assessing long-term lipid peroxidative damage to proteins in vivo. Methylphosphate was increased by MTX and infliximab (p<0.05): It reduce transcription of inflammatory genes and decrease RNAs affinity to nuclear phosphoprotein. 7 beta-hydroxycholesterol was reduced by infliximab (p<0.05). It is present at elevated concentrations in inflammatory lesions, strongly cytotoxic and pro-oxidative. Its effect is relevant on cell death and oxidative DNA damage. Conclusions: Biochemicals involved in a number of pathways showed some promising and subtle trends and better elucidate the pathogenetic mechanisms of the disease and response to treatments. MTX and Infliximab treatment of CD4+ cells had an impact on inflammation and cellular defence. This is the first demonstration of metabolites that can be monitored for treatment efficacy and tolerability. These observations provide some insights into the potential mechanisms involved in mediating the anti-inflammatory and the immunomodulation effects of MTX and infliximab. Disclosure of Interest: None Declared